Sarcomatoid carcinoma of the urinary bladder: A case report and short review of the literature - Kölükçü, Engin; Kılıç, Şahin; Uluocak, Nihat; Atılgan, Doğan; Deresoy, Faik Alev (Journal of Surgery and Medicine, 2019)
Although the most common malignant formations in the bladder are urothelial carcinomas, there are also tumors with different differentiation degrees like sarcomatoid carcinoma of the urinary bladder. It is a rare and highly aggressive type of tumor and consists of malignant epithelial and sarcomatous components. The literature about the subject is extremely limited, and there is no consensus on treatment protocols. This case report aims to present a case of 71-year-old man who presented with macroscopic hematuria and diagnosed with sarcomatoid carcinoma of the urinary bladder.